The Impact of Local Revenue and Capital Expenditure on Economic Growth and the Education Sector in East Lombok Regency - Moh Suhaidi; Nurul Mi'raj (Cigarskruie: Journal of Educational and Islamic Research, 2025)
This study aims to analyze the effect of Regional Original Revenue (PAD) and capital expenditure on economic growth and its implications on the education sector in East Lombok Regency, West Nusa Tenggara. The sample used included the entire area of ​​East Lombok Regency in the 2017 to 2022 period. The data analysis method used was multiple linear regression with a classic assumption test. The results of the analysis show that partially, regional original income has no significant effect on economic growth, as evidenced by the value of SIG 0.131> 0.05 in a negative direction. Meanwhile, the capital expenditure variable also has no significant effect on economic growth, with a value of Sig 0.108> 0.05 and a positive direction. Simultaneously, PAD and Capital Expenditures jointly have a significant effect on economic growth in East Lombok Regency, which is indicated by the value of SIG 0.223> 0.05. In relation to the education sector, the results of this study indicate that the ineffectiveness of PAD and capital expenditure in encouraging economic growth can have an impact on the allocation of the education budget and the quality of educational services in the area. With the contribution of PAD and capital expenditure of 38.2% to economic growth, there are still 61.8% of other factors that influence, including education and investment policies of human resources. These findings underline the importance of more optimal regional financial management strategies to encourage economic growth while improving the quality of education.